Inovações tecnológicas e perenização da degradação sistêmica do trabalho: a contrarreforma da previdência social com enfoque para o trabalho no setor rural - Souza, Edvnia Angela de [UNESP]; Thomaz Junior, Antonio [UNESP]; Carvalhal, Marcelo Dornelis [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2022)
This article discusses the setbacks in Brazilian Social Security since the counter-reform occurred in 2019. This situation is even worse when it is considered the main feature of the labour market in this country: a high proportion of the working class is in informal employment and, as a result, enormous obstacles to making contributions to secure access to pensions, especially in rural areas. The paper also analyses the effects of the previous counter-reform in the Employment and Social Security policies adopted in 2017, as well as the challenges faced by the rural labour force in the context of increased use of new technological tools, digitalisation and information sources in agricultural production. Those challenges had been a distinctive feature of the capital expansion before the COVID-19 pandemic, showing its relevance in the (post)pandemic period. As final remarks, the work highlights the historical context of capital development in which (re)definitions of the power and control of the work is predominant in global geopolitics. Therefore, the counter-reform of social rights, the elimination of social protection mechanisms and the neoliberal rationales are related to a more general capital movement promoting widened productivity, cost reductions and capital accumulation rates by controlling work and nature.
Technological innovations and precarious employment: analysis of the social security counter-reform of work in the rural sector
Keywords: Employment and Social Security; Rural Work; 4.0 Industry; Neoliberalism